Fabrication of a 3D carbon electrode for potential dielectrophoresis-based hepatic cell patterning application using carbon micro-electrical-mechanical system (CMEMS). (1st May 2022) - Wan Yahya, Wan Nurlina; Ibrahim, Fatimah; Thiha, Aung; Jamaluddin, Nurul Fauzani; Madou, Marc
Abstract: Cell patterning of hepatocyte cells is one of the techniques to construct liver tissue engineering. This work presents the development of a 3D carbon dielectrophoresis (carbonDEP) microfluidic chip for cell patterning using carbon micro-electrical-mechanical system microfabrication approach. The new design of electrode named interdigitated radiating-strips electrode (IRSE) was fabricated to generate positive DEP (pDEP) force for cell patterning mimicking the biological hepatic lobule. The electrical characterization of the fabricated carbon electrode shows that the average electrode resistivity is 4.61 ± 1.19 × 10 −4 Ω m which is low enough to generate effective DEP force using 10 of volts. Results also show the shrinkage of the SU-8 structures during pyrolysis which gives impact to the final dimension of the carbon electrode. The functioning of the DEP microfluidic chip was demonstrated through DEP polystyrene microbeads patterning as a model of hepatocyte cells. 3D carbon IRSE presents a 67% increase in trapping efficiency of pDEP microbeads as compared to the planar carbon IRSE and the microbeads were pattern along the electrical field induced to form a hepatic lobule mimicking pattern. These results suggest that the 3D carbonDEP microfluidic chip has a great potential to be used for 3D hepatic cells patterning for liver tissue engineering applications.